Implementação da metodologia BIM no setor elétrico e modelagem tridimensional de subestações - Matos, Pamela (2021)
Project management, expansion, maintenance and replacement of equipment in national electric power substations is still largely based on two-dimensional Computer-Aided Design (CAD) files. The present work was developed during an R&D between the University of Passo Fundo and the CEEE Group in order to help companies in the electricity sector to improve the visualization and presentation of substation arrangements, whether existing or new. This is done by three-dimensional modeling and the use of BIM (Building Information Model) methodology, through the REVIT® software. However, this is still not widely used in the sector, but it can bring benefits and add reliability to design techniques by making use of the generation of links between objects and masses, in addition to the Clash Detection tools (interference detection), which make it possible to increase the agility and execution of tasks, improving the assembly of the arrangements and reducing the risk of failures in the design of new substations. To enable the complete design of the arrangement, simplified blocks were used to represent the assets with visual acuity, without processing overhead due to the high number of elements. For this purpose, only seven main blocks of families were used, with a view to favoring a cleaner and agile processing. To enable the implementation of constructive planning techniques, modeling of electromechanical equipment and creation of the virtual library, the arrangements of three electrical energy substations in the concession area of the State Company of Electricity Generation and Transmission (CEEE - GT) were reconstructed. they are generically called Substation A, Substation B and Substation C, having their degrees of complexity and number of elements scaled in decreasing. The results show that it is possible to carry out the modeling of equipment with simple geometries and visual identification is met, in addition to being possible to have the entire arrangement from terrain to complete equipment with minimum required computational configurations.